Mechanical Thrombectomy for Acute Ischemic Stroke Secondary to Infective Endocarditis. (9th November 2017) - Ambrosioni, Juan; Urra, Xabier; Hernández-Meneses, Marta; Almela, Manel; Falces, Carlos; Tellez, Adrian; Quintana, Eduard; Fuster, David; Sandoval, Elena; Vidal, Barbara; Tolosana, Jose M; Moreno, Asunción; et al.
Abstract: Intravenous thrombolysis is contraindicated in acute ischemic stroke secondary to infective endocarditis. We report our initial experience in 6 cases of proximal vessel occlusion treated with mechanical thrombectomy, which was safe (no bleeding) and effective (significant early neurological improvement) and might be useful in this clinical setting.